SATISFACTION OF UMRAH PILGRIMS IN UMRAH AND HAJJ PLUS TRAVEL ARMINAREKA PERDANA JEMBER - Rahayu, Jekti (Jurnal Mebis, 2023)
Indonesia gets a very large quota for Umrah pilgrims, making a lot of Umrah travel mushrooming and having intense competition in creating satisfaction for the pilgrims. The case of ignored pilgrims makes some people worry about choosing travel and having low trust in them. This study aims to analyze the satisfaction of Umrah pilgrims of Arminareka Perdana Jember with a quantitative approach. Samples were taken of 238 respondents with a simple random sampling approach. Research data was obtained by distributing digital and printed questionnaires to pilgrims who had completed Umrah. Data were analyzed using the Partial Least Squares (PLS) analysis technique. The results of the analysis show that there is a strong relationship between several research variables on the satisfaction of Umrah pilgrims, which are price perception, service quality and trust. Improvements in price perceptions, service quality and trust led to an increase in the satisfaction of Umrah pilgrims.